EFISIENSI PEGADAIAN SYARIAH DAN PROSPEK PERTUMBUHAN ASET DI INDONESIA - Roikhan, Roikhan (al-Uqud : Journal of Islamic Economics, 2017)
The purpose of this study is to analyze the efficiency of Islamic Pawnshop together with four competitors and analyze the prospects for assets growth of the Islamic pawnshop in Indonesia. This study is quantitative analyze research with secondary data of annual financial statements from the Islamic Pawnshop and four competitors during 2008-2014. The sampling technique is the purposive sampling with sample of the Islamic Pawnshop and four competitors in Indonesia. This study uses analysis efficiency of the Data Envelopment Analysis method. Input variables are: the load bonus, deposit wadiah, general and administrative expenses, salaries and allowances, and other expenses, and the output variables are: murabaha margin revenue, other services revenues, and loan qardh. Then this study uses analyze prospects based on System Dynamics methods. The results showed efficiency of Islamic Pawnshop can reach value of 100 percent for 2008-2014 compared to its competitors that reach only 97.42 percent. And the prospect of an asset for Islamic Pawnshop can get optimistically in 2025 to reach Rp 116 trillion in the presence of inorganic action.Â